2005
DOI: 10.1111/j.1365-2567.2005.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific autoantigens in Sjögren's syndrome by SEREX

Abstract: SummaryWe carried out SEREX (serological analysis of antigens by recombinant cDNA expression cloning) using sera from patients with Sjögren's syndrome (SjS) and investigated the frequencies of autoantibodies against autoantigens identified by SEREX in the sera of healthy individuals (HI) and patients with SjS, rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). IFI16 and two kelch-like proteins, KLHL12 and KLHL7, were found to be novel autoantigens in SjS by SEREX. A markedly high frequency of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 31 publications
2
48
2
Order By: Relevance
“…13 No other clinical implications of altered function of KLHL7 have been reported, but antibodies have been detected in patients with Sjögren syndrome. 14 In the present family, Schirmer test revealed no signs of dry eye, which is associated with Sjögren syndrome.…”
Section: Commentmentioning
confidence: 91%
“…13 No other clinical implications of altered function of KLHL7 have been reported, but antibodies have been detected in patients with Sjögren syndrome. 14 In the present family, Schirmer test revealed no signs of dry eye, which is associated with Sjögren syndrome.…”
Section: Commentmentioning
confidence: 91%
“…IFI16 is a target for autoantibodies and several studies have shown the presence of anti-IFI16 autoantibodies in chronic autoimmune diseases such as SLE [64], systemic sclerosis [65], rheumatoid arthritis [66] and Sjö gren's syndrome [67]. IFI16 is known to relocalise from the nucleus to the cytosol following UV treatment or viral DNA detection.…”
Section: Disease Related Roles Of the Pyhin Proteinsmentioning
confidence: 99%
“…Overexpression of IFI16 drives early steps of an inflammatory response through NF-kB mediated secretion of proinflammatory molecules such as ICAM1, E-selectin, IL-8 and MCP-1 [14,15]. Autoantibodies against IFI16 are present in the sera of patients with systemic sclerosis (SSc) [16], systemic lupus erythematosus (SLE) [17,18], rheumatoid arthritis (RA) [19,20] and Sjö gren's Syndrome (SS) [19]. Recently, it has also been discovered as serum circulating protein in the same autoimmune diseases [21].…”
Section: Introduction: the Interferon Inducible 16 (Ifi16) Proteinmentioning
confidence: 99%